Hypothermia protects the brain from transient global ischemia/reperfusion by attenuating endoplasmic reticulum response-induced apoptosis through CHOP. - Xiaojie Liu (Public Library of Science (PLoS), 2013)
Endoplasmic reticulum (ER) stress has been implicated in the pathology of cerebral ischemia. Apoptotic cell death occurs during prolonged period of stress or when the adaptive response fails. Hypothermia blocked the TNF or Fas-mediated extrinsic apoptosis pathway and the mitochondria pathway of apoptosis, however, whether hypothermia can block endoplasmic reticulum mediated apoptosis is never known. This study aimed to elucidate whether hypothermia attenuates brain cerebral ischemia/reperfusion (I/R) damage by suppressing ER stress-induced apoptosis. A 15 min global cerebral ischemia rat model was used in this study. Terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) positive cells in hippocampus CA1 were assessed after reperfusion of the brain. The expressions of C/EBP-homologous protein (CHOP) and glucose-regulated protein 78 (GRP78) in ischemic hippocampus CA1 were measured at 6, 12, 24 and 48 h after reperfusion. The results showed that hypothermia significantly attenuated brain I/R injury, as shown by reduction in cell apoptosis, CHOP expression, and increase in GRP78 expression. These results suggest that hypothermia could protect brain from I/R injury by suppressing ER stress-induced apoptosis.